Analysis of Ethical Violations in Financial Accounting Practices (Case Study of PT Hanson International Tbk) - Barreto, Angelica Lena Graça; Trisnaningsih, Sri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study analyzes ethical violations in accounting practices at PT Hanson International Tbk, which were revealed in 2016. The case began when the Financial Services Authority (OJK) imposed a fine of IDR 5 billion on the President Director, Benny Tjokrosaputro, due to improper revenue recognition and lack of transparency in financial reports. This study uses a case study method with data collection through literature reviews and analysis of official documents and OJK reports. The results of the study show that unethical accounting practices not only harm the company but also have a negative impact on the trust of investors and other stakeholders. The involvement of external auditors from the Public Accounting Firm (KAP) Purwanto, Sungkono & Surja (PSS) in this case reflects a violation of the professional code of ethics. This study emphasizes the importance of integrity and compliance with ethical standards in preventing similar violations from occurring in the future. Recommendations for strengthening the internal control system and ethics education in the accounting environment are also presented as preventive measures.